2023
DOI: 10.3389/fpls.2023.1226072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of doubled haploid lines derived from different cycles of the Iowa Stiff Stalk Synthetic (BSSS) maize population

Abstract: Molecular characterization of a given set of maize germplasm could be useful for understanding the use of the assembled germplasm for further improvement in a breeding program, such as analyzing genetic diversity, selecting a parental line, assigning heterotic groups, creating a core set of germplasm and/or performing association analysis for traits of interest. In this study, we used single nucleotide polymorphism (SNP) markers to assess the genetic variability in a set of doubled haploid (DH) lines derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…In contrast, Labate et al [18] and Hinze et al [19] observed a significant decrease in the mean number of alleles per locus and expected heterozygosity in the BSSS and BSCB1 populations after 12 and 15 cycles of reciprocal RS, respectively. A decrease in marker diversity (in terms of the number of polymorphic loci, mean number of alleles per locus, expected heterozygosity, or observed heterozygosity) within maize populations that underwent various numbers of RS cycles has also been reported in several previous studies [7,14,[20][21][22][42][43][44][45][46][47].…”
Section: Diversity Statistics and Allele Frequencysupporting
confidence: 63%
“…In contrast, Labate et al [18] and Hinze et al [19] observed a significant decrease in the mean number of alleles per locus and expected heterozygosity in the BSSS and BSCB1 populations after 12 and 15 cycles of reciprocal RS, respectively. A decrease in marker diversity (in terms of the number of polymorphic loci, mean number of alleles per locus, expected heterozygosity, or observed heterozygosity) within maize populations that underwent various numbers of RS cycles has also been reported in several previous studies [7,14,[20][21][22][42][43][44][45][46][47].…”
Section: Diversity Statistics and Allele Frequencysupporting
confidence: 63%
“…Additionally, inbreeding from landraces results in a high load of recessive alleles, mutations, and deleterious alleles that need to be selected against by conventional breeding methods ( Strigens et al., 2013 ). According to Ledesma et al. (2023) , the 17 cycles of reciprocal recurrent selection program have left behind useful genetic variation present in the C0_DHL during the selection process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selected DH lines could be introgressed into current germplasm to improve the adaptation to high plant density. The large genetic distances of the C0_DHL compared to the C17_DHL ( Ledesma et al., 2023 ) demonstrated the potential of the C0_DHL group to broaden the genetic base of the Stiff Stalk (SS) germplasm. However, more studies need to be conducted at the testcross level to know the hybrid combinations’ performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations